Mutation analysis of PRSS1, SPINK1 and CFTR gene in patients with alcoholic and idiopathic chronic pancreatitis: A single center study - Şişman, Gürhan; Tuğcu, Murat; Ayla, Kerimova; Sebati, Özdemir; Şentürk, Hakan (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: A relation between some genetic mutations and chronic pancreatitis (CP) has been reported. However, the relation of genetic mutation to alcoholic CP (ACP) and idiopathic CP (ICP) still remains controversial. In this study, we investigated the prevalence of protease serine 1 (PRSS1), serine protease inhibitor, Kazal type 1 (SPINK1) SPINK1 and cystic fibrosis transmembrane conductance regulator (CFTR) mutations in ACP and ICP patients in Turkey. Materials and Methods: Forty-one patients with ACP and 38 patients with ICP were enrolled, and 35 healthy individuals served as controls. The PRSS1 and SPINK1 mutations were investigated by the polymerase chain reaction (PCR)-restriction fragment-length polymorphism (RFLP) technique. The CFTR mutation was examined with PCR direct sequencing. Results: The mean ages of the ACP, ICP and healthy control groups were 53.2, 40.4 and 46.3 years, respectively. A CFTR F508 mutation was detected as a heterozygote in one (2.4%) patient with ACP. In the ICP and control populations, PRSS1, SPINK1 and CFTR mutations were not detected. Conclusion: This study shows that PRSS1, SPINK1 and CFTR mutations do not play a role in ACP and ICP patients.